Making education work : areas of concern in Philippine education, education and manpower development programs. (Quezon City, Philippines : Congressional Oversight Committee on Education, 1993)
The four books comprising the entire report of the Congressional Commission on Education (EDCOM) are the product of a twelve-month intensive study of the state of education and training in the Philippines... Books One and Two look at the education scene in depth: the first, in terms of areas of concern that seem to be true of all types and levels of eduction; the second, in terms of the levels of education... Book Three capsulizes views, and suggestions from multi-sectoral groups who are the givers and receivers of education services... Book Four comprises selected technical papers by academics, professionals and field managers who participated actively in EDCOM consultations as well as thoughtful discourses from EDCOM resource persons and consultants.
Part I. Education and manpower development programs -- Chapter 1. General framework -- Chapter 2. Goals and structure of Philippine education -- Chapter 3. Access and equity -- Chapter 4. Quality and relevance -- Chapter 5. Language of instruction -- Chapter 6. The Education of teachers -- Chapter 7. Non-formal education -- Chapter 8. Special topics and concern -- Part II. Conclusions and recommendations.
Includes bibliographical references and index.
Keywords: EDUCATION